Stigmatizing attitude towards mental illness, disabilities, emotional and behavioural disorders, among healthcare students in a Tropical University College of Health Sciences - Ifeoma Adaigwe Amaechi; Paul Osemeke Nwani; Augustine Onyebuchi Akadieze (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Stigma toward mental illness (MI), physical disability (DA), and emotional/behavioral disorders (EBD) has been identified as a form of violence and a cause of nontake-up of help by people in need. Stigmatization can aggravate an individual's feeling of rejection and incompetence and can be detrimental to treatment-seeking and adherence behaviors. This study evaluated the attitude of healthcare students toward MI, DA, and EBDs. MATERIALS AND METHODS: This study employed a cross-sectional survey method. A disproportionate stratified sampling technique was used to recruit participants. Sixty five consenting students who met the inclusion criteria were consecutively recruited from each clinical department of the college. The students were selected from the five clinical departments of the College (Nursing sciences, Medical Rehabilitation, Radiography, Medical laboratory science, and Medicine). The questionnaires on stigmatizing attitudes toward MI, EBD, and DA were self-administered. Descriptive statistics of frequency count, percentage, range, mean, and standard deviation were used to summarize participants' sociodemographic data and their questionnaire scores. Inferential statistics of Spearman rank order correlation was used to test for correlation; Mann-Whitney U test was used to test the influence of gender, religion, and family history; and Kruskal-Wallis test was used to test the influence of department of study and level of study. Alpha level was set at 0.05. RESULTS: Three hundred twenty seven students comprising 164 (50.2%) males and 163 (49.8%) females participated. Mean age of participants was 22.89 ± 2.05 years. 45.3% of the participants reported positive family history of one or a combination of MI, DA, and EBDs. The study observed poor attitude toward MI and fair attitude toward DA and EBD. There were significant correlations between attitudes toward MI and disability (r = 0.36, P = .000033), MI and EBD (r = 0.23, P = .000023), disability and EBD (r = 0.46, P = .000001), and age and attitude toward disability (r = 0.15, P = .009). Females had significantly more positive attitude toward disability (P = .03) and EBDs (P = .03). Nursing students also demonstrated the most positive attitudes toward MI (P = .03) and EBD (P = .000416), while final year students demonstrated the most positive attitudes toward MI (P = .00145) and EBDs (P = .03). CONCLUSIONS: There was a poor attitude toward MI and a fair attitude toward DA and EBD. Attitude toward MI, DA, and EBD correlated significantly with one another. Older students, females, and higher levels of training in the healthcare profession were associated with more positive attitudes toward MI, DA, and EBDs.